2021
DOI: 10.1093/ofid/ofab173
|View full text |Cite
|
Sign up to set email alerts
|

Discordance of the Repeat GeneXpert MTB/RIF Test for Rifampicin Resistance Detection Among Patients Initiating MDR-TB Treatment in Uganda

Abstract: Background The Global Laboratory Initiative (GLI) guidelines recommend to repeat GeneXpertMTB/RIF (XpertMTB/RIF) in patients with a low-pretest probability of rifampicin-resistance (RR). Design/Methods In a cross-sectional study using results of sputum specimens collected from participants screened for the STREAM 2 trial. We recruited all patients with XpertMTB/RIF RR-TB detected who were referred for RR/MDR-TB treatment init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The most commonly used molecular tests were Hain MTBDRplus, MTBDRsl and the GenXpert systems. Regarding the GenXpert, its performance is less optimal when the assay is performed in paucibacillary samples and low RIF-resistance settings, see for example [28,29,36], where the authors reported false-positive results. In those conditions, it is recommended to repeat the Xpert testing in case of a first positive result.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most commonly used molecular tests were Hain MTBDRplus, MTBDRsl and the GenXpert systems. Regarding the GenXpert, its performance is less optimal when the assay is performed in paucibacillary samples and low RIF-resistance settings, see for example [28,29,36], where the authors reported false-positive results. In those conditions, it is recommended to repeat the Xpert testing in case of a first positive result.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that 15/96 (15.6%) isolates had a discordant RR result between the initial and repeated XpertMTB/RIF testing and that 10/96 (10.4%) isolates were falsepositive RR isolates. A low bacillary load on the initial sputum was four times more likely to produce discordant RR results upon repeating the XpertMTB/RIF test [28].…”
Section: Xpert Mtb/rif Xpert Mtb/rif Ultra and Xpert Mtb/xdrmentioning
confidence: 96%